Peningkatan Produktivitas dan Efisiensi Konsumsi Air Tanaman Bayam (Amaranthus tricolorL.) pada Teknik Hidroponik melalui Pengaturan Populasi Tanaman - Ade Wachjar; Rizkiana Anggayuhlin (Departemen Agronomi dan Hortikultura, 2013)
The purpose of the research was to study the effect of plant population on productivity and water consumption of amaranth in hydroponic technique. Research was conducted in Parung Farm, Bogor, from April to May 2011. The research used Nutrient Film Technique (NFT) hydroponic system that modificated with gravel as its planting medium. The research was arranged in Randomized Complete Block Design with one factor, i.e. , 1, 2, 3, or 4 seedling numbers per hole. The research was divided into two experiment. The first was experiment to study the effect of plant population on plant productivity, and the second was experiment to study the effect of plant population on water consumption of plant. The result showed that plant with one seedling in the planting hole gave the best response on growth of amaranth (plant height, leaves numbers), but for plant productivity, the best result was obtained from plant with three seedlings in the planting hole. Water consumption was highest in plants with one seed per planting hole. Apparently, the more the population, the less consumption of water is needed. This is due to poor root conditions in densely populated. Plant roots will adversely affect the absorption of water.Keywords : gravel, hydroponic kit, seedling numbers, the planting hole